IMPROVING SPEAKING SKILL THROUGH VIDEOS FOR JUNIOR HIGH SCHOOL STUDENTS - Dini Hidayati (Dialectical Literature and Educational Journal, 2019)
The aims of this research are: (1) to find out the use of video to improve the students’ speaking ability and (2) to find out the strengths and weaknesses of the use of video to improve the students’ speaking skills. This research was a classroom action research. To collect the data, the researcher used observation, interview, and the speaking test. The study reports that (1) the use of videos can improve the students’ speaking ability. The mean score of speaking skill in pre-test was 47,62, cycle I was 62,14 and cycle II was 75,95. (2) The use of video in the teaching of speaking had some strengths and weaknesses. The strength of video were the students felt enjoy when they watched the video and the students could get the ideas to speak from the real environment of the speaker. The weakness of video were less serious when they did a discussion, it made the situation on the class were noisy and were still awkward in using video as one of technology based English learning technique.